Migration and potential risk of trace phthalates in bottled water : a global situation - Luo, Qiong (2020)
Increasing attention has been dedicated to trace phthalates in bottled water due to the serious concerns on public health, while there is still a lack of systematic analysis and assessment of current global situation. Through analyzing five representative phthalates in bottled water over 20 countries, this work clearly revealed the phthalates-associated potential risks in both human daily intake and estrogenic effect. In the risk assessment, the kinetic models were also developed to describe and predict phthalates migration. In more than three hundred brands of bottled waters from twenty one countries, the detection frequency of the five targeted phthalates was found to be in the order of dibutyl phthalate (DBP, 67.6%), di-2-(ethyl hexyl) phthalate (DEHP, 61.7%), diethyl phthalate (DEP, 47.1%), benzyl butyl phthalate (BBP, 36.9%), and dimethyl phthalate (DMP, 30.1%). Among the countries studied relating concentrations of DEHP in bottled waters, the top five countries ranked in the order of high to low were Thailand, Croatia, Czech Republic, Saudi Arabia and China with an average level of 61.1, 8.8, 6.3, 6.2 and 6.1 μg/L, respectively. The average levels of BBP, DBP, DMP and DEP in bottled water from Pakistan were high, in which DEP and DMP were ranked 1st among all countries with the average levels of 22.4 and 50.2 μg/L, while BBP and DBP were ranked 2nd and 3rd with the average levels of 7.5 and 17.8 μg/L, respectively. The human daily intake-based risk assessment revealed that phthalates in bottled waters studied would not pose a serious concern on public health. However, the adverse estrogenic effects of phthalates in bottled water from some countries appeared to be significant. This study just shed light on global situation of phthalates in bottled water, and more efforts should be needed to systematically examine the phthalates-related safety of bottled water.